2021
DOI: 10.3389/fendo.2021.636182
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Proliferation for the Expansion of Stem Cell-Derived Pancreatic Cells: Advantages and Limitations

Abstract: Restoring the number of glucose-responsive β-cells in patients living with diabetes is critical for achieving normoglycemia since functional β-cells are lost during the progression of both type 1 and 2 diabetes. Stem cell-derived β-cell replacement therapies offer an unprecedented opportunity to replace the lost β-cell mass, yet differentiation efficiencies and the final yield of insulin-expressing β-like cells are low when using established protocols. Driving cellular proliferation at targeted points during s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…In addition, quantification of anti‐Ki67 antibody labeling revealed that 30% of the cells in the bioprinted construct were still in the active phase of the cell cycle 12 days after printing (Figure 2H). This observation is in line with the proliferation rate of human pluripotent stem cells that were differentiated into pancreatic progenitors and have been found to contain the replication marker Ki67 at 30%–50% (reviewed in reference [ 50 ] ).…”
Section: Resultssupporting
confidence: 76%
“…In addition, quantification of anti‐Ki67 antibody labeling revealed that 30% of the cells in the bioprinted construct were still in the active phase of the cell cycle 12 days after printing (Figure 2H). This observation is in line with the proliferation rate of human pluripotent stem cells that were differentiated into pancreatic progenitors and have been found to contain the replication marker Ki67 at 30%–50% (reviewed in reference [ 50 ] ).…”
Section: Resultssupporting
confidence: 76%
“…On the other hand, modeling adaptive proliferation of adult β cells with SC-β has potential advantages but also some weaknesses that should be addressed. Basal proliferation of SC-β is usually defined as “low” but is still much higher than that of native adult human β cells (1% vs. 0.2–0.5%) [ 331 , 332 ]. It is possible that future improvements in differentiation protocols will enhance SC-β maturity bringing the proliferation rate close to that of adult β cells.…”
Section: Classification Of Processes Associated With β Cell Dysfunctionmentioning
confidence: 99%
“…Using b-cell lines and mice, Ansarullah et al showed that inceptor interacts with the receptors for insulin and insulin growth factor 1 to promote their internalization via clathrin-mediated endocytosis, protecting b cells from autocrine/paracrine stimulation by their own insulin (14). Knockout of the inceptor gene in mice enhances b-cell proliferation and mass-a critical finding that could help to increase bcell numbers for diabetes therapy (15). In addition, if inceptor is found in other insulin-sensitive tissues, blocking it could facilitate a reversal of insulin resistance.…”
Section: Novel Insights Into the Mechanism Of Insulin Secretionmentioning
confidence: 99%